Evolution of Darwin's Peloric Gloxinia (Sinningia speciosa) Is Caused by a Null Mutation in a Pleiotropic TCP Gene. (27th April 2018) - Dong, Yang; Liu, Jing; Li, Peng-Wei; Li, Chao-Qun; Lü, Tian-Feng; Yang, Xia; Wang, Yin-Zheng
Abstract: Unlike most crops, which were domesticated through long periods of selection by ancient humans, horticultural plants were primarily domesticated through intentional selection over short time periods. The molecular mechanisms underlying the origin and spread of novel traits in the domestication process have remained largely unexplored in horticultural plants. Gloxinia ( Sinningia speciosa ), whose attractive peloric flowers influenced the thoughts of Darwin, have been cultivated since the early 19th century, but its origin and genetic basis are currently unknown. By employing multiple experimental approaches including genetic analysis, genotype–phenotype associations, gene expression analysis, and functional interrogations, we showed that a single gene encoding a TCP protein, SsCYC, controls both floral orientation and zygomorphy in gloxinia. We revealed that a causal mutation responsible for the development of peloric gloxinia lies in a 10-bp deletion in the coding sequence of SsCYC . By combining genetic inference and literature searches, we have traced the putative ancestor and reconstructed the domestication path of the peloric gloxinia, in which a 10-bp deletion in SsCYC under selection triggered its evolution from the wild progenitor. The results presented here suggest that a simple genetic change in a pleiotropic gene can promote the elaboration of floral organs under intensive selection pressure.